Self-evaluation processes of schools or internal evaluation of the system? - Sousa, Anabela Barros Pinto; Terrasêca, Manuela (Education Policy Analysis Archives, 2015)
Evaluation, in the current context of education policy, is an instrument of regulation of action. In Portugal, public schools evaluation focuses on the dimensions of self-evaluation and external evaluation, the articulation of both being normatively imposed and also encouraged in various evaluation, benchmarking, and monitoring initiatives. Based on document analysis of background documents and reports of evaluation of schools initiatives, this article presents the various concepts of school self-evaluation in those documents and reflects on the "self" dimension of this self-evaluation in Portuguese public schools as an exercise of autonomy and accountability. Since 2002, the guidelines for self-evaluating schools are known. Although the administrations continue to say that it is not intended to induce the process, models and tools for evaluating schools, particularly the External Evaluation of Schools (EES), have been carrying a soft orientation / regulation, since they call for the school to produce a discourse built around the analysis of dimensions that they impose. This "new form of governance", assuming itself as a form of regulation of this action, can become a form of self-evaluation as a discourse, more or less standardized, which is a part of (self)-evaluationt of the system, rather than a process of construction of negotiated and shared references in school. We aim to characterize this self-evaluation, from the EES's conceptual framework analysis, and study the dimensions in which it is applied, as well as to clarify its place in the evolution of the EES model.